2020
DOI: 10.1149/1945-7111/ab64bf
|View full text |Cite
|
Sign up to set email alerts
|

Review—Single Walled Carbon Nanotubes as Optical Sensors for Biological Applications

Abstract: Since the discovery of the band gap fluorescence from single walled carbon nanotubes (SWNT) many advancements have been made towards the use of these unique fluorophores as optical biosensors in vitro, ex vivo in vivo. Attention has been given to these pure carbon structures due to their photostability, tunable properties, and bright near infrared emission that falls in the tissue transparency window. This review highlights some of the major advancements in the field of SWNT biosensors over the last two decade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 107 publications
(200 reference statements)
0
38
0
Order By: Relevance
“…SWCNT@PEG-D-naphthoate has significantly lower fluorescence emission intensity except for (8,3)-and (6,5)-chiralities. J) normalized fluorescence emission for the (7,5) chirality at an excitation wavelength of λex = 650 nm reveals shifts in the emission wavelength (SWCNT@PEG-D-naphthyl (blue), SWCNT@PEG-D-naphthoate (red), SWCNT@PEG-Dpentyl (yellow), SWCNT@PEG-D-hexanoate (purple)).…”
Section: Resultsmentioning
confidence: 99%
“…SWCNT@PEG-D-naphthoate has significantly lower fluorescence emission intensity except for (8,3)-and (6,5)-chiralities. J) normalized fluorescence emission for the (7,5) chirality at an excitation wavelength of λex = 650 nm reveals shifts in the emission wavelength (SWCNT@PEG-D-naphthyl (blue), SWCNT@PEG-D-naphthoate (red), SWCNT@PEG-Dpentyl (yellow), SWCNT@PEG-D-hexanoate (purple)).…”
Section: Resultsmentioning
confidence: 99%
“…For these reasons, they have been intensively studied for optical and electronic applications. [252][253][254] Shin et al reported PEDOT/CNTs with core-shell structure, synthesized by emulsion polymerization; [255] dodecylbenzene sulfonic acid was used as surfactant. When added to water, both CNTs and EDOT precursors associated into micelles; EDOT was then polymerized by the addition of FeCl 3 .…”
Section: Carbon Nanotubesmentioning
confidence: 99%
“…Single walled nanotubes (SWNTs) have attracted great interest due to their promising mechanical, chemical, and thermal properties and high surface area [1][2][3][4][5]. In recent years, there have been several experimental and theoretical studies showing the potential applications of SWNTs [6][7][8][9][10][11][12]. Applications include the use of SWNTs in energy storage and energy conversion devices [13,14], high-strength composites [15][16][17], nanoprobes and sensors [18][19][20], actuators [21,22], electronic devices [23,24], catalysis [25,26], and hydrogen storage media [27,28].…”
Section: Introductionmentioning
confidence: 99%